2015
DOI: 10.1111/ggi.12579
|View full text |Cite
|
Sign up to set email alerts
|

Association of sarcopenic obesity with the risk of all‐cause mortality: A meta‐analysis of prospective cohort studies

Abstract: Many prospective studies have investigated the relationship between sarcopenic obesity (SO) and risk of mortality. However, the results have been controversial. The aim of the present study was to evaluate the association between SO and all-cause mortality in adults by a meta-analysis of prospective cohort studies. A systematic literature search was carried out through electronic databases up to September 2014. A total of nine articles with 12 prospective cohort studies, including 35 287 participants and 14 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(153 citation statements)
references
References 56 publications
4
135
0
14
Order By: Relevance
“…Baillargeon et al [6] reported that older men with testosterone deficiency who were treated with testosterone therapy had a reduced risk of rehospitalization. Furthermore, patients with sarcopenic obesity appear to have a significantly increased risk of all-cause mortality [4] . While the relationship between testosterone deficiency and sarcopenic obesity remains unclear, low endogenous testosterone levels are associated with a greater risk of allcause mortality [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baillargeon et al [6] reported that older men with testosterone deficiency who were treated with testosterone therapy had a reduced risk of rehospitalization. Furthermore, patients with sarcopenic obesity appear to have a significantly increased risk of all-cause mortality [4] . While the relationship between testosterone deficiency and sarcopenic obesity remains unclear, low endogenous testosterone levels are associated with a greater risk of allcause mortality [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Because of their increased disability and dependence on others, frail older individuals experience reduced QoL and increased morbidity, resulting in institutionalization and increased mortality [4][5][6][7] . For these reasons, frailty is a public health threat with a serious economic impact -in light of an increasing life expectancy and the financial challenges facing health care systems worldwide.…”
mentioning
confidence: 99%
“…In contrast, in a study using data from the NHANES III study, older women with sarcopenia had a higher risk of all-cause mortality, independent of obesity [62]. A recent meta-analysis demonstrated that sarcopenic obesity is associated with a 24% increase in the risk of all-cause mortality compared to patients without sarcopenic obesity, particularly in men [63]. …”
Section: Impact Of Sarcopenic Obesity On Morbidity and Mortalitymentioning
confidence: 99%
“…17 The term sarcopenic obesity is used in the literature to describe the increase of abdominal obesity accompanied by reduced muscle mass in men undergoing ADT 18 and is found to be associated with an increase in all-cause mortality. 19 The underlying mechanisms of increased abdominal fat with ADT are not well understood. Visceral adipocytes are known to have androgen receptors and it has been proposed that testosterone might be directly involved in fatty acid mobilization.…”
Section: Adt and Obesitymentioning
confidence: 99%